Transcriptional Enhancers in the Regulation of T Cell Differentiation - Nguyen, Michelle L. T.; Jones, Sarah A.; Prier, Julia E.; Russ, Brendan E. (Frontiers in Immunology, 2015)
The changes in phenotype and function that characterise the differentiation of naïve T cells to effector and memory states are underscored by large-scale, coordinated, and stable changes in gene expression. In turn, these changes are choreographed by the interplay between transcription factors and epigenetic regulators that act to restructure the genome, ultimately ensuring lineage-appropriate gene expression. Here, we focus on the mechanisms that control T cell differentiation, with a particular focus on the role of regulatory elements encoded within the genome, known as transcriptional enhancers. We discuss the central role of transcriptional enhancers in regulating T cell differentiation, both in health and disease.